Identification of River Water Pollution Based on Saprobic Index of Macrozoobenthos in Anggokoine River, Oheo Sub-District North Konawe District - La Baco Sudia; La Ode Ahmad Nur Ramadhan; Kahirun; La Ode Muhammad Erif; Surya Cipta Ramadhan Kete; Lalu Darwite (University of Jember, 2023)
Study of identification of water pollution based on Macrozoobenthos Saprobic index identify was carried out. The aims of the research are to identify types of macrozoobenthos existing on the Anggokoine River and to identify river water pollution condition based on macrozoobenthos saprobic index at the Anggokoine River. The method used in the research is the direct observation method, collection of primary and secondary data. Analysis of Macrozoobenthos Saprobic Index used the Ravera (1979) Index and also water pollution index for the physicochemical characteristic of river water. The result at the research reveals that the Anggokoine river was categorized as mildly polluted based on physicochemical condition. It was found that 14 kinds of benthos which consist of six families with Bivalvia, Pelecypods and Gastropoda classes. Based on Macrozoobenthos Saprobic Index at Station I and II, it was analyzed that the Saprobic Index value is 2.6 and 2.6 namely categorized as α-Mesosaprobic and it is indicated that the Anggokoine river is heavily polluted. Station III it was analyzed that the Saprobic Index value is 2.3 namely categorized as β-Mesosaprobic and it is indicated that Anggokoine river is have polluted.